Factors affecting the accuracy and precision of potentiometric titration of weak acid mixtures by multiple linear regression analysis - Chaiyavat Chaiyasut (Chulalongkorn University, 2013)
Thesis (M.Sc. in Pharm)--Chulalongkorn University, 1996